Behavior Analysis of Using Sunscreen to Protect Skin from The Sun - Ketut Kwartantaya Winaya; Made Satria Primandita; Nikmah Nuur Rochmah; Elisa Issusilaningtyas; Fadli (Jurnal Penelitian Pendidikan IPA, 2024)
Excessive exposure to UV rays can increase the risk of skin cancer, premature aging, and other skin problems. As such, raising awareness of the risks of UV rays is a priority in an effort to encourage more proactive behavior in protecting the skin from the negative effects of sunlight. The aim of the study was to analyze the factors that influence individual behavior in sunscreen use as part of skin protection practices from sun exposure, and how these factors vary by cultural, social, and economic context. An analytical survey with a cross sectional approach was conducted in this study with a total of 180 correspondents consisting of adolescents aged 12-16 years from several junior high schools in Jambi City. The results showed that the factors that influence individual behavior in using sunscreen include knowledge, socioeconomic and cultural factors. This study can make a significant contribution to efforts to prevent skin cancer and protect the skin from damage due to UV exposure.